"Impure in Their Motive for Establishment": Mission Schools as the Unintended Catalysts of Nationalism and Culturally Relevant Education in Colonial Korea - Spargo, Eric. (Tufts University. Tisch Library., 2021)
Thesis (M.A.)--Tufts University, 2021.; Submitted to the Dept. of History.; Advisor: Gary Leupp.; Committee: Man Xu, and Sung-Yoon Lee.; Keywords: History, and Education history.